Genome-wide analysis of HACD family genes and functional characterization of GhHACD2 for very long chain fatty acids biosynthesis in Gossypium hirsutum - Yan, Minwen; Xi, Hongyuan; Hu, Shiyin; Song, Jikun; Jia, Bing; Feng, Pan; Yang, Liupeng; Ma, Jianjiang; Wang, Li; Pei, Wenfeng; Zhang, Bingbing; Yu, Jiwen; et al. (Frontiers in Sustainable Food Systems, 2024)
Cotton (Gossypium spp.) not only serves as a primary textile fiber crop but also as a vital oilseed crop. It stands as the world's fifth-largest oil crop and is rich in essential fatty acids. At present, the mechnisms underlying the biosynthesis of cottonseed oil have been extensively studied in cotton. 3-Hydroxyacyl-CoA dehydratase (HACD) is the third rate-limiting enzyme in the elongase complex, which plays a critical role in the biosynthesis of Very Long Chain Fatty Acids (VLCFA). However, the members of the HACD family and their roles in cottonseed oil remain uncharacterized in cotton. This study identified that G.arboreum and G.raimondii have 2 HACD genes, while 4 HACD genes exists in G.hirsutum, and G.barbadense. The phylogenetic relationships of the 12 HACD genes from the four cotton species further divided them into two subfamilies. Gene structure and conserved motif analysis revealed that members of the HACD family were relatively conserved during the evolution of cotton, but members within the same subfamily exhibited more similar structures. Homology and collinearity analysis suggest whole-genome duplication/segmental duplication may be a key factor in the amplification of the cotton HACD gene family. The qRT-PCR analysis of high-oil and low-oil genotype found significant differences in the expression levels of GhHACD1-4, which indicates GhHACD1-4 is expected to participate in the lipid oil biosynthesis process. Subcellular localization experiments confirmed the presence of the GhHACD2 inendoplasmic reticulum. The KEGG pathway enrichment analysis of co-expressed genes of GhHACD1 and GhHACD2 genes were conducted to confirm their potential involvement in fatty acid elongation and oil biosynthesis. Furthermore, transgenic overexpression analysis of GhHACD2 caused a 5.02% decrease in oil content compared with the control in yeast, while the levels of C28:0, C30:0, and VLCFAs were significanly improved. This study characterizes HACD gene family members in cotton and provides rich genetic resources for increasing cottonseed oil content and improving the nutritional value of cottonseed oil.